New DSM-5 category 'unspecified catatonia' is a boost for pediatric catatonia: review and case reports. (August 2013) - Dhossche, Dirk M; Goetz, Michal; Gazdag, Gabor; Sienaert, Pascal
SUMMARY The creation in DSM-5 of a new category 'unspecified catatonia' aspires to improve diagnosis and treatment of catatonia in patients of all ages without diagnosable major psychotic, affective or medical disorders. Unspecified catatonia may be particularly beneficial in boosting recognition and treatment of pediatric catatonia that often occurs outside these disorders. Until now, pediatric catatonia has been poorly recognized. Benzodiazepines and electroconvulsive therapy are underutilized in pediatric catatonia, yet are safe and effective treatments without the risk of worsening catatonia or precipitating neuroleptic malignant syndrome. Unspecified catatonia should be considered when catatonic symptoms are present in children and adolescents with autistic and other developmental disorders, autoimmune encephalitides, tic disorders (with or without self-injury) and Tourette's syndrome, Kleine–Levin syndrome, post-traumatic reactions, pervasive refusal syndrome and other disorders. The aspirations of the 'unspecified catatonia' category to reduce morbidity and mortality and to increase further research are bound to be tested in the field of pediatric catatonia over the next few years. Changes in DSM-5 regarding the classification of catatonia are reviewed. Case reports are presented to illustrate the use of the new category, unspecified catatonia, in children and adolescents.